2006
DOI: 10.2174/156720206776875821
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Changes of the Retina and Choroid in Systemic Lupus Erythematosus: Pathology and Pathogenesis

Abstract: Systemic lupus erythematosus (SLE) is a chronic autoimmune disorder that affects multiple organ systems. When eyes are involved, the principle manifestations are hemorrhage, retinal cotton wool spots, microangiopathy and vaso-occlusion. Research in the past two decades has significantly contributed to our understanding about this disease in general and its therapeutic management, although knowledge about the mechanism of ocular involvement and pathogenesis in SLE is limited. This is an important issue, because… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 58 publications
1
26
0
Order By: Relevance
“…(B) Survival was also monitored from six to ten months of age. trolled formation of autoantibodies, leading to the excess formation of immune complexes that deposit in different tissues, causing inflammation and tissue damage [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…(B) Survival was also monitored from six to ten months of age. trolled formation of autoantibodies, leading to the excess formation of immune complexes that deposit in different tissues, causing inflammation and tissue damage [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 550 patients with SLE, Stafford-Brady and colleagues observed retinopathy in 41 patients (7.1%) [6], while a study of children with SLE reported ocular involvement in 35% of patients [7]. In the case of our patient, histopathologic examination of the peripheral retina revealed many small occluded vessels, some appearing similar to changes seen in chronic retinal vasculitis [8]. The vascular occlusive findings and cobblestone degeneration are likely the consequence of SLE vasculopathy and lupus anticoagulant thrombosis.…”
Section: Discussionmentioning
confidence: 57%
“…Additionally, choroidal vasculature may be damaged by fibrin deposition, which often occurs in the vessel wall and lumen. 8,9 The choroid has been shown to be affected in patient of SLE in several experimental and clinical studies. [10][11][12][13][14][15][16] Enhanced depth imaging optical coherence tomography (EDI-OCT), which is a recent modification of the standard OCT technique, offers a noninvasive, rapid, objective, and reliable diagnostic modality for the imaging of choroidal alterations and allows in vivo examination and quantification of the choroid.…”
mentioning
confidence: 99%